ChemInform Abstract: Modulation Effect of Interlayer Spacing on the Superconductivity of Electron‐Doped FeSe‐Based Intercalates. Issue 24 (June 2015) - Hayashi, Fumitaka; Lei, Hechang; Guo, Jiangang; Hosono, Hideo
Abstract: Na/DA and Sr/DA intercalates of FeSe (DA: (H2 N)Cn H2n (NH2 ) with n = 0, 2, 3, or 6 as electron sources and molecular spacers) are prepared by a low‐temperature ammonothermal method using Na, Sr, FeSe, and condensed NH3 (high‐pressure glass vessel, 273‐298 K, 2‐3 h) followed by the removal of intercalated NH3 (evacuation at 303‐373 K).